Dialog Teori Konflik Dialektika-Fungsional Meneropong Dinamika Sidang Itsbat di Indonesia - Nihayatur Rohmah (Proceedings of Annual Conference for Muslim Scholars, 2018)
The difference in starting and becoming a hijriya month seems to be a question that does not go away. Whether we realize it or not, these things are part of the life of this nation. Therefore, an understanding of the root of existing problems can be helpful in determining attitudes. Determination of the 1st of Ramadan has become a tradition in this country will be decided by the government through Itsbat assembly of Islamic mass organizations in the ministry of Religion. The problem of hisab rukyat in terms of determining the beginning of the month of Qamariyah-especially Ramadan, Syawwal and Dzulhijjah-syndrome raised numbers, sometimes even inflaming the evil permutations that tore the fabric of ukhuwwah Islamiyyah. Government efforts through the trial basically rests on the efforts to achieve uniformity, prosperity and unity of Indonesian Muslims. In 2012 Muhammadiyah provides a firm stance that will not be able to oblige it with a variety of reasons between belief and belief between Muhammadiyah and the Government. From that fact, according to Lewis A Coser the conflict stems from an imbalance (imbalance) in the overall sosial system, the imbalance that causes splits (plague); this split inspires the emergence of the international (temporary integration); it is this temporal system that causes the structure to increase flexibly; this flexible structure then overcomes these imbalances through conflict; and reveals the highest level of adaptability in circumstances